The life and works of W.G. Collingwood : a wayward compass in Lakeland - Craig, Malcolm (Psychologist) (Archaeological lives., 2018)
This well researched biography provides a comprehensive account of the life and works of William Gershom Collingwood (1854-1932), a 19th century polymath whose story should be better known. He was a noted friend and colleague of John Ruskin, whose secretary he later became.